THE DYNAMICS OF STRUCTURAL CHANGES OF BROILER CHEST MUSCLES ON EARLY TERMS AFTER SLAUGHTER - Коцюмбас, Г. І.; Щебентовська, О. М.; П’ятничко, О. М.; Коляда, Х. О. (Scientific Progress & Innovations, 2013)
The article presents the dynamics of morphological changes of broiler chest muscles after slaughter. The terms of rigor mortis development and structural changes of muscle tissue were tested in the process of broiler meat ripening. It was set that autolysis of white group of muscles is occurring gradually, but is developing quickly enough. In 4 hours after slaughter the changes, observed in muscle tissue, are typical for early stages of autolysis, achieving the maturity in 24 hours after slaughter.